2018
DOI: 10.2967/jnumed.117.202861
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dose Calibrators for 68Ga PET Imaging: Unexpected Findings in a Multicenter Clinical Pretrial Assessment

Abstract: We report the discovery of a systematic miscalibration during the work-up process for site validation of a multicenter clinical PET imaging trial using Ga, which manifested as a consistent and reproducible underestimation in the quantitative accuracy (assessed by SUV) of a range of PET systems from different manufacturers at several different facilities around Australia. Sites were asked to follow a strict preparation protocol to create a radioactive phantom with Ga to be imaged using a standard clinical proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…This will include certification of 68 Ga‐PSMA‐11 and 177 Lu‐PSMA‐617 production and 68 Ga PET/CT camera validation. The 68 Ga‐PSMA‐11 quality control parameters have been replicated from the Movember/PCFA ProPSMA study . 68 Ga‐PSMA‐11 administration and PET/CT acquisition are standardized across sites according to the study nuclear medicine manual.…”
Section: Methodsmentioning
confidence: 99%
“…This will include certification of 68 Ga‐PSMA‐11 and 177 Lu‐PSMA‐617 production and 68 Ga PET/CT camera validation. The 68 Ga‐PSMA‐11 quality control parameters have been replicated from the Movember/PCFA ProPSMA study . 68 Ga‐PSMA‐11 administration and PET/CT acquisition are standardized across sites according to the study nuclear medicine manual.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, accuracy of four different types of radionuclide calibrators was investigated for 68 Ga by using well-calibrated gamma spectrometry. The results were surprising in that all the radionuclide calibrator systems showed a systematic error in the range of 10-25% [76,146]. It was reported that the deviations were mainly due to the incorrect factory-shipped dose calibrator setting.…”
Section: Production For the Clinical Applicationsmentioning
confidence: 98%
“…Recent studies [9][10][11] demonstrated large measurement deviations ( > ± 10%) for several individual diagnostic radionuclides commonly used (particularly for 111 In and 68 Ga). However, no large multi-center studies have reported on the impact of radionuclide calibrator accuracy on activity measurements in the increasing application of personalized molecular radiotherapy based on a theranostic approach.…”
Section: Introductionmentioning
confidence: 99%